Pengaruh Pembelajaran Model Flipped Classroom berbantu Google Slide terhadap Hasil Belajar IPA Siswa Sekolah Dasar - Olga Mar'atus Sholikhah; Fitri Alyani (Postgraduate, University of Mataram, 2022)
This study purpouse to determine whether or not there is an effect of the flipped classroom learning model assisted by google slides on improving student learning outcomes in science learning materials of style and motion in everyday life. In this study, quantitative experiments using the Quasi-Experimental method and the Posttest - Only Control Group design were used to determine the increase in science learning outcomes. The sample of this study consisted of 64 fourth grade elementary school students who were divided into 2 classes, namely the experimental class and the control class. Data were analyzed using t-test statistical data. The results of the analysis that has tested based on the t-test show that there is a significant difference in learning outcomes in science with the flipped classroom learning model assisted by google slides. Based on the results of the research analysis and discussion, it shows that the flipped classroom learning model assisted by google slides can affect the science learning outcomes of style and motion material in everyday life in fourth grade elementary school students.